Simuler pour changer la conception et les rapports sociaux de conception du travail : un commentaire sur les dispositifs de simulation de l’activité dans les organisations - Pascal Ughetto (Activités)
The article discusses the contributions made to this issue on activity simulation. Focusing on the simulation of activity within organizations, it argues that the methods in question potentially affect power relations in change management processes. In these processes, participatory approaches do not always manage to take work activity into account. Simulation methods seek to take the constraints of the activity seriously and to consider the resources that would be useful.